A concept analysis of holistic nursing care in paediatric nursing - A.A. Tjale; J. Bruce (AOSIS, 2007)
Holistic nursing care is widely advocated and is espoused in the philosophy of the South African Nursing Council. This concept is unclear, variously interpreted and poorly understood in paediatric nursing. This study was undertaken to examine the meaning of holistic nursing care and to develop a framework for holistic nursing care, which can be utilised in nurse education settings and in clinical nursing practice in the context of paediatric nursing. A qualitative, interpretive, explorative and contextual research design was used. An evolutionary concept analysis was undertaken to clarify the concept "holistic nursing care" in paediatric nursing in three Johannesburg hospitals. Rodgers' (1989, 2000) evolutionary method was utilised to analyse the concept.